Shiva Linga - Temples of India Project Team (Jio Institute, 2024)
Inside the mahamandapa (pillared hall), in its northeastern corner, rests a black Shiva linga (aniconic representation of Shiva) on a yonipatta (womb-shaped base slab) dating from a later period. A loose sculpture of a seated Nandi is also kept inside the mahamandapa, near the antarala (vestibule or antechamber), and features a prominent hump.